Blood Pressure Profile in Children with Sickle Cell Anaemia as seen at a Tertiary Health Facility in Enugu, South-east Nigeria, West African Sub-region - Ikechukwu O. Okongwu; Ngozi Mbanefo; Daberechi Kenneth Adiele; Ifunanya Okongwu; Anthony N. Ikefuna; Michael Okoeguale Ibadin (Nigerian Journal of Medicine)
Introduction: Sickle cell anaemia (SCA) is prevalent in Nigeria and affected children are predisposed to several complications. Amongst these are morbidities involving the cardiovascular system which ordinarily should predispose them to hypertension (HTN). Fortuitously, however, hypotension rather than HTN was commonly reported in children with SCA. Recently, the rising incidence of HTN amongst such patients is being noted, especially when ambulatory blood pressure (BP) monitoring is done. There are therefore conflicting the reports on the BP profile of children with SCA. The study was undertaken to correctly determine the BP profile of children with SCA. Methods: The cross-sectional and comparative study was undertaken at the University of Nigeria Teaching Hospital, Enugu, over an eight-month period. It involved 212 participants aged 3–17 years (106 subjects with HbSS and 106 age/gender matched controls with haemoglobin genotype AA). Sociodemographic, clinical and anthropometric parameters were obtained using a semi-structured questionnaire. BP was measured using Accoson mercury sphygmomanometer. Mann–Whitney U, Chi-square, Student’s t and Fisher’s exact tests (where appropriate) were used to evaluate the intergroup and intragroup associations. Results: A significant proportion of subjects had systolic and diastolic BP (DBP) readings that were below the 50th centile (70.8% and 61.3%, respectively). Only 1 (0.9%) subject had DBP above the 95th centile. Compared with controls, there was a significant difference in the systolic BP (SBP) of subjects (χ2 = 9.09, P = 0.01). Subjects were approximately two times less likely than controls to have a SBP readings that are within <50th centiles (odds ratio, [95% confidence interval], 0.43 [0.22–0.84]). However, there was similar distribution of DBP (P = 0.10). Although not statistically significant, mean SBP (mSBP) and mean DBP (mDBP) in subjects were higher than values in controls. (95.51 ± 12.25 mmHg vs. 94.25 ± 11.23 mmHg [mSBP] and 58.25 ± 8.05 mmHg vs. 56.56 ± 8.03 mmHg [mDBP]). Conclusions: Subjects with SCA have BP profile that is predominantly <50th centile. Compared to controls; however, subjects had higher mSBP and mDBP. Recommendations: Patients with SCA should be monitored more frequently for HTN since this study shows that their BP profile is relatively higher than that of their genotype AA counterparts.